WITHDRAWN: Hard Carbon Wrapped in Graphene Networks as Lithium Ion Battery Anode. (1st December 2018) - Zhang, Xiang; Fan, Changling; Li, Lingfang; Zhang, Weihua; Zeng, Wei; He, Xing; Han, Shaochang
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief. The article is a duplicate of a paper that has already been published in Materials Letters 138 (2015) 259-261, https://doi.org/10.1016/j.matlet.2014.10.023 . One of the conditions of submission of a paper for publication is that authors declare explicitly that the paper is not under consideration for publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.